Blind student aces exam - New Straits, Times (New Straits Times, 2016)
PUTRAJAYA: Travelling 40km to school every day did not stop visually impaired Azree Feekree Zamzuri from acing his Sijil Tinggi Persekolahan Malaysia (STPM) examination.